INVESTIGATING THE NANOCRYSTALLINITY OF SOL GEL DERIVED TiO2 NANOPARTICLES UPON ANNEALINGAND POST HYDROTHERMAL TREATMENTS - Akhmad Herman Yuwono; Alfian Ferdiansyah; Arif Rahman; Wulandari Handini (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
INVESTIGATING THE NANOCRYSTALLINITY OF SOL GEL DERIVED TiO2 NANOPARTICLES UPON ANNEALINGAND POST HYDROTHERMAL TREATMENTS. The present study is aimed at investigating the major factor causing the low nanocrystallinity nature of the sol gel derived TiO2 nanoparticles. For this purpose, TiO2 nanoparticles of different nanocrystallinity was synthesized by various hydrolysis ratio (Rw) of 0.85; 2.00 and 3.50 upon sol solution preparation, followed with subsequent drying, conventional annealing and post-hydrothermal treatments. The resulting nanoparticles were studied by dynamic light scattering, XRD and FT-IR spectroscopy which confirm that the highly amorphous state of TiO2 is related to the fast development of stiff Ti-OH networks during hydrolysis and condensation upon sol gel process. A post hydrothermal treatment involving high-pressure water vapor has been successfully devised to enhance the nanocrystallinity of TiO2 nanoparticles. It has been found in this study that Rw value of 2.00 was the optimum hydrolysis ratio during sol solution preparation of TiO2 precursor to result in the most enhanced nanocrystallinity as represented with the biggest crystallite size of 12.46 nm.